Characterization of the autophosphorylation property of HflX, a ribosome‐binding GTPase from Escherichia coli. Issue 7 (8th June 2016) - Ghosh, Aditi; Dutta, Dipak; Bandyopadhyay, Kaustav; Parrack, Pradeep
Abstract : Escherichia coli HflX belongs to the widely distributed but poorly characterized HflX family of translation factor‐related GTPases that is conserved from bacteria to humans. A 426‐residue polypeptide that binds 50S ribosomes and has both GTPase and ATPase activities, HflX also exhibits autophosphorylation activity. We show that HflX(C), a C‐terminal fragment of HflX, has an enhanced autophosphorylation activity compared to the full‐length protein. Using a chemical stability assay and thin layer chromatography, we have determined that phosphorylation occurs at a serine residue. Each of the nine serine residues of HflX(C) was mutated to alanine. It was found that all but S211A retained autophosphorylation activity, suggesting that S211, located in the P‐loop, was the likely site for autophosphorylation. While the S211A mutant lacked the autophosphorylation site, it possessed strong GTP binding and GTPase activities. Abstract : E. coli HflX, a ribosome‐binding GTPase, has an autophosphorylation activity that is enhanced when its N‐terminal domain is deleted. For the C‐terminal domain of HflX, autophosphorylation requires divalent cations, with Mn 2+ and Mg 2+ being most effective. The site of autophosphorylation is Ser211, located in the G1 motif (P‐loop) of HflX.